Determinants of Perceptions Towards Life and Health Insurance Plans Among Students of Faculty of Science and Technology, Universiti Sains Islam Malaysia - Fayzah Addawiyah Binti Othman; Rose Irnawaty Ibrahim (Department of Mathematics and Statistics Universiti Putra Malaysia, 2024)
Vol 45 No 1 (2023)